Breast cancer knowledge and perception among health care professionals and senior medical students at Bolan Medical Complex Hospital Quetta, Pakistan - Pari Gul Jogezai; Mahwash Mansoor; Palwasha Gul; Zara Arshad (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To assess knowledge and perception about different aspects of Breast Cancer among health care professionals at Bolan Medical Complex Hospital Quetta, Pakistan. Methods: This cross-sectional study was carried out at Bolan Medical Complex Hospital Quetta from October to December 2017. A total of 312 health care workers including consultants (42), residents (85), medical officers (52), interns (45), nurses (48) and final year medical students (40) took part in the study. The study tool was a self-designed questionnaire with separate sections to assess the knowledge about risk factors, signs and symptoms, screening tools, breast self-examination (BSE), treatment and barriers in seeking medical advice. Results: Participants had satisfactory knowledge about risk factors and signs of breast cancer but poor knowledge about association of breast cancer with menarche status, oral contraceptive pills and smoking. Majority was aware of mammography benefits and believed that breast cancer is curable with therapy. All perceived that cultural and socioeconomic barriers are the cause of late stage presentation. The nurses particularly were having misconceptions in knowledge about breast cancer risk factors and screening tools. Conclusion: The current study demonstrated that knowledge related to breast cancer was average and highlighted the need for provision of continuing medical education programs to improve health practitioners' practice on cancer screening tools. Knowledge was particularly deficient regarding screening modalities and BSE method and timing. Special emphasis is needed to train nurses, so they could play an expanded role in breast cancer care. Keywords: Breast Cancer, Pakistan, Risk Factors, Awareness, Continuous...